2015
DOI: 10.1097/md.0000000000000724
|View full text |Cite
|
Sign up to set email alerts
|

Ethmoid Osteoma as a Culprit of Orbital Emphysema

Abstract: Orbital emphysema is generally recognized as a complication of orbital fractures involving any paranasal sinuses. The recognition about its etiology has extended beyond sole trauma, but few articles mentioned tumors to be a possible cause.In this case report, we present a patient with orbital emphysema associated with ethmoid osteoma without orbital cellulitis or trauma history. The patient developed sudden proptosis, eyelid swelling, and movement limitation of the left eye, peripheral diplopia, and left perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The first category is the result of pressure effect of the tumor including proptosis, orbital pain, diplopia, decrease in visual acuity, palpable mass and epiphora. The second category includes clinical findings secondary to sinusitis which may be the result of obstruction or damage to the involved sinus and presenting as orbital emphysema, orbital cellulitis and subperiosteal abscess formation adjacent to the involved sinus 2‐6,8 . The orbital extension of the infection in some reports was suggested that occurred via the bony erosion of the tumor and involvement of the orbital periosteum 5,9 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first category is the result of pressure effect of the tumor including proptosis, orbital pain, diplopia, decrease in visual acuity, palpable mass and epiphora. The second category includes clinical findings secondary to sinusitis which may be the result of obstruction or damage to the involved sinus and presenting as orbital emphysema, orbital cellulitis and subperiosteal abscess formation adjacent to the involved sinus 2‐6,8 . The orbital extension of the infection in some reports was suggested that occurred via the bony erosion of the tumor and involvement of the orbital periosteum 5,9 .…”
Section: Discussionmentioning
confidence: 99%
“…The second category includes clinical findings secondary to sinusitis which may be the result of obstruction or damage to the involved sinus and presenting as orbital emphysema, orbital cellulitis and subperiosteal abscess formation adjacent to the involved sinus. [2][3][4][5][6]8 The orbital extension of the infection in some reports was suggested that occurred via the bony erosion of the tumor and involvement of the orbital periosteum. 5,9 On the other hand, an intact periosteum has been shown in cases of orbital invasion of infection, suggesting that the sinus contents may gain access to the orbit not only via the emissary vessels and nerves but also through the paper like thin medial wall of the orbit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 39 Alotaibi describes the case of an osteoma of the anterior ethmoidal cells sized 30 × 25 × 15 mm growing in the direction of the orbit, which was excised endoscopically using neuronavigation, as in the case of the tumour sized 30 × 20 × 15 mm described by Zhuang. 12 , 36 Endoscopic excision of osteomas from the ethomoid cells is recommended, but insufficient when the lesions spread outside the sinuses. 40 Karbassi draws attention to the cases, described in the literature, of giant osteomas in the ethomoid region removed endoscopically, which were not accompanied by orbital complications.…”
Section: Discussionmentioning
confidence: 99%